Sambandet mellan levnadsstandard och miljöprestation i hög- respektive låginkomstländer En kvantitativ analys - Bjuvberg,Fredrik; Ohlén,Matilda (2026)
This study investigates the relationship between standard of living and environmental performance by analyzing the components of standard of living: income per capita, educational level, and life expectancy across both high- and low-income countries. The study finds a positive correlation between standard of living and environmental performance in all countries. However, this relationship is only statistically significant in high-income countries, where all components of standard of living show a positive impact. Among these components, education emerges as the most influential factor, as it remains the only statistically significant variable in the multiple regression analysis. This highlights the importance of education as the key driver of environmental performance in high-income countries. In low-income countries, no significant correlation is observed, which could be attributed to the prioritization of immediate societal needs over environmental concerns. The study suggests that education plays a crucial role in shaping environmental awareness and political efficacy, which allows for the implementation of more ambitious environmental policies. The findings highlight the need for further research to understand the specific conditions in low-income countries and the importance of adapting climate policies to these unique circumstances.
Keywords: Levnadsstandard; miljöprestation; environmental kuznets curve; postmaterialistisk teori; moderniseringsteori; inkomst per invånare; utbildningsnivå; förväntad livslängd; pågående konflikt; korruption; demokrati